Idea Carla Schmitta w dorobku Wiesława Kozuba-Ciembroniewicza - Citkowska-Kimla, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article aims at presenting Wiesław Kozub-Ciembroniewicz’s interest in Carl Schmitt’s ideas. First, the possibilities of getting acquainted with Schmitt’s political philosophy by Kozub-Ciembroniewicz were described. Then, the academic activity of Kozub-Ciembro niewicz is presented in which Schmitt’s inspirations were visible. The next part discusses the works in which Kozub-Ciembroniewicz wrote about the German philosopher of law.
Keywords: Kozub-Ciembroniewicz, Wiesław; Schmitt, Carl; totalitarianism; nazism; fascism